2008
DOI: 10.1038/sj.jid.5701207
|View full text |Cite
|
Sign up to set email alerts
|

Lysophospholipid Receptor-Mediated Calcium Signaling in Human Keratinocytes

Abstract: The lysophospholipids, sphingosine-1-phosphate (S1P) and lysophosphatidic acid (LPA), stimulate chemotaxis and induce differentiation of human keratinocytes. As Ca(2+) plays an important role in keratinocyte differentiation, we studied Ca(2+) signaling by S1P and LPA in these cells, known to express mRNA transcripts of the S1P(1-5) and LPA(1-3) receptors, and the receptor subtypes involved in this process. S1P and LPA caused transient increases in intracellular free Ca(2+) concentration ([Ca(2+)](i)), with pEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…In a few studies, however, it has been also used as an S1P 3 receptor antagonist. For example, as mentioned above, Lichte et al (2008), reported that S1P-induced calcium signaling in human keratinocytes is mainly mediated by S1P 3 , because it can be blocked by the putative S1P 3 antagonists BML-241, and VPC23019. Recently, Jongsma et al (2009), using three different assays, have shown that several compounds of the VPC series, including VPC23019, behave as full or partial agonists at S1P 3 receptors.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In a few studies, however, it has been also used as an S1P 3 receptor antagonist. For example, as mentioned above, Lichte et al (2008), reported that S1P-induced calcium signaling in human keratinocytes is mainly mediated by S1P 3 , because it can be blocked by the putative S1P 3 antagonists BML-241, and VPC23019. Recently, Jongsma et al (2009), using three different assays, have shown that several compounds of the VPC series, including VPC23019, behave as full or partial agonists at S1P 3 receptors.…”
mentioning
confidence: 90%
“…Two studies that used higher BML-241/CAY10444 concentrations (50 and 100 μM) did observe an antagonist effect. In one of these studies, the S1P 1 agonist SEW2871 had no effect, while the S1P 1 /S1P 3 receptor antagonist VPC23019 reproduced the effect of BML-241/CAY10444 (Lichte et al, 2008). In the other study, B-cell migration was promoted by a mixed S1P 1 /S1P 3 receptor agonist (VPC24191), but not by the S1P 1 agonist SEW2871.…”
mentioning
confidence: 99%
“…Binding of LPA to its specific receptors also elicits mobilization of intracellular calcium (Ca 2+ i ) from IP 3 -dependent stores and influx of extracellular Ca 2+ (Ca 2+ o ) mediated by incompletely defined mechanisms (Noguchi et al , 2009). Keratinocytes are known to express LPA 1–3 and respond to LPA with Ca 2+ transients (Anliker and Chun, 2004; Roedding et al , 2006; Ross et al , 2007; Lichte et al , 2008), but the physiological relevance of LPA-induced Ca 2+ fluxes and the downstream signaling pathways in mediating specific physiological effects remain to be defined.…”
Section: Introductionmentioning
confidence: 99%
“…Heightened levels of intracellular Sphingosine-1-phosphate (S1P) increase cytosolic Ca 2+ levels by direct mobilization of Ca 2+ from Thapsigargin (TG) sensitive stores (Meyer zu Heringdorf, et al, 2003), while increases in extracellular S1P concentrations activate Store Operated Calcium Entry (SOCE), through activation of G-protein coupled receptors (Mehta, et al, 2005). In keratinocytes, increased intracellular S1P enhances keratinocyte growth and differentiation, and blocks apoptosis (Hong, et al, 2008; Lichte, et al, 2008). Activating sphingosine kinase (SPHK1) increases intracellular S1P; thus, agents that activate this enzyme enhance expression of the differentiation markers filaggrin and involucrin in HaCAT keratinocytes (Hong, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%